Achieving Air Quality Goals at Minimum Cost - Robert E. Kohn (Washington University Law Quarterly, 1968)
In this Article, Robert E. Kohn presents a minimum cost method of achieving air quality goals—that is, the economic criteria for pollution reduction, given a permissible level of emissions. Through the use of a simplified model, Kohn explains the operation of a much more complex approach to air quality control developed through research conducted under grants from the Public Health Service of the United States Department of Health, Education and Welfare.
Keywords: Pollution